DIFFERENCES IN THE LEARNING ABILITY OF MALE AND FEMALE STUDENT IN WRITING DESCRIPTIVE SKILLS OF GRADE X STUDENTS OF SMAN 4 KEDIRI - Inge Aprilia Saputri; Rika Riwayatiningsih; Dewi Kencanawati (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
This study aims to determine differences in the ability to write descriptive text. From male students to female students, students of class X SMAN 4 Kediri. This type of research is quantitative because it collects data using numbers. The sample class studied was one, namely class X-1, which consisted of 30 people, 13 male and 17 female. The research instrument used was a written test given to students when collecting the data. The results of the research show that the ability to write descriptive text among class X students at SMAN 4 Kediri, namely between male and female students, is indeed different. Based on the average calculation, male students got a score of 43.0763 (44) while the average score for female students was 65.1765 (66). So it can be concluded that the difference in their writing abilities is significant; this can be seen from the SPSS calculation results from the independent t-test.